Personal Security Tracking based on Android and Web Application - Angry Ronald; Violitta Yesmaya; Muhammad Danaparamita (Universitas Ahmad Dahlan, 2018)
Nowadays, the frequency of abduction is increasing significantly. Information technology provide many social media which is causing the leaked of personal information where abductor can find out the information. Using social media, people can share location, life event, and anything related about their life event, these become the useful information for the abductor. To anticipate this, a lot of personal tracking device is developed, but the response is too late. Because, the family or relative of the victims will notice that abduction had happen after the victim is lost. According to the problem, this research will focus on develop the personal tracking device which trigger by the victims who own the phone based on android and web application. Whenever the abduction happens, the victim just need to click the button and the system will send a message to the relatives and family in their contact also trigger the notification to the local security. Software development life cycle that will be used is scrum which is divided into several processes like backlog, sprints, scrum meetings, and demos. The result of this research is android application for user and web application for managing application.